A Peptide-Nucleic Acid Targeting miR-335-5p Enhances Expression of Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) Gene with the Possible Involvement of the CFTR Scaffolding Protein NHERF1 - Anna Tamanini; Enrica Fabbri; Tiziana Jakova; Jessica Gasparello; Alex Manicardi; Roberto Corradini; Alessia Finotti; Monica Borgatti; Ilaria Lampronti; Silvia Munari; Maria Cristina Dechecchi; Giulio Cabrini; et al. (Biomedicines, 2021)
(1) Background: Up-regulation of the Cystic Fibrosis Transmembrane Conductance Regulator gene (CFTR) might be of great relevance for the development of therapeutic protocols for cystic fibrosis (CF). MicroRNAs are deeply involved in the regulation of CFTR and scaffolding proteins (such as NHERF1, NHERF2 and Ezrin). (2) Methods: Content of miRNAs and mRNAs was analyzed by RT-qPCR, while the CFTR and NHERF1 production was analyzed by Western blotting. (3) Results: The results here described show that the CFTR scaffolding protein NHERF1 can be up-regulated in bronchial epithelial Calu-3 cells by a peptide-nucleic acid (PNA) targeting miR-335-5p, predicted to bind to the 3′-UTR sequence of the NHERF1 mRNA. Treatment of Calu-3 cells with this PNA (R8-PNA-a335) causes also up-regulation of CFTR. (4) Conclusions: We propose miR-335-5p targeting as a strategy to increase CFTR. While the efficiency of PNA-based targeting of miR-335-5p should be verified as a therapeutic strategy in CF caused by stop-codon mutation of the CFTR gene, this approach might give appreciable results in CF cells carrying other mutations impairing the processing or stability of CFTR protein, supporting its application in personalized therapy for precision medicine.